Sanitation of sweet orange through micrografting - Kanwar, Jyoti; Kaul, M K; Singh, P P; Naruka, I S (Indian Horticulture, 2019)
Micrografting technique was used for the development of virus free nursery in Sweet Orange cv. Blood Red Malta. The micrografting was carried out using 11- 20 days old etiolated seedlings of Rough Lemon, Sour orange, Carrizo and Karna Khatta rootstocks. An apical meristem (1-2 mm) having 3-leaf primordial (0.3-0.5 mm) was placed on aseptically grown rootstocks making an inverted ‘T’ incision in vitro. Micrografts were inoculated on MS media added with auxins. Highest grafts success (60%) was recorded when apical meristems grafted on 13 days old Carrizo seedlings were used as rootstock. Scion treated with 2,4-D at 3.0 mg/l exerted maximum positive effect on the success of STG (70%). Successful micrografts were hardened under controlled conditions and further shifted in insect proof net house to develop disease free mother progeny.